Strategi Kebijakan Kesehatan dan Upaya Pencegahan HIV/AIDS Pada Wanita Pekerja Seks (WPS) : Literature Review - Daniar Dwi Ayu Pamela; Ira Nurmala (Dian Nuswantoro Semarang, 2021)
HIV/AIDS is a health problem that has a global impact, one of the causes is proper prevention efforts. HIV prevention must be followed by the implementation of appropriate health policy strategies in each country. The purpose of this study is to identify and identify health policies of HIV/AIDS prevention behavior in FSW. The method of writing a literature review begins with selecting a topic, determining keywords and making journal references. The databases used include Google Scholar, Elsevier, Pubmed. The search for references was limited from 2016 to 2020. The keywords used were “Strategy, Health Policy, Prevention, HIV/AIDS, Female Sex Workers”. A total of 25 articles were included in the availability and 8 articles were included in the discussion. Factors that affect HIV/AIDS prevention in FSW are low knowledge of HIV, inability to negotiate factors, violence, commercial sex for more than 1 year with a partner of 2-3 people for a night. Health policy strategies in various countries are adapted to the needs of FSW according to guidelines, such as improving reproductive health services, VCT, condom distribution and peer support. HIV-based innovation programs such as zoning for localization areas, health promotion from a religious perspective and the DIFFER strategy. All risk factors that need to be considered in determining the HIV/AIDS strategy in FSW by considering advocacy in the region.